Phylogenetics of the plant genera Dracaena and Pleomele (Asparagaceae) - Lu, Pei-Luen; Morden, Clifford (Botanica Orientalis: Journal of Plant Science, 2011)
This research focuses on the biodiversity and the evolutionary history of the world-wide medicinal plant genus, Dracaena, and the plant genus Pleomele. The debate concerning the relationship between Dracaena and Pleomele has continued till date - some botanists continue to include Pleomele within Dracaena but others claimed to separate the two genera. Dracaena is a genus comprising of about 40-100 species world wide, mainly in tropics and subtropics, with the exception of America. Pleomele is a genus that has been circumscribed consisting of 10-50 species in Asia. Till date, its center of biodiversity is unknown. Pleomele is only classified well in Hawaii, but confused with Dracaena in the other parts of Asia. Phylogenetic relationship among the 33 taxa within the Dracaena and Pleomele were reconstructed. DNA sequences from the chloroplast DNA intergenic spacer, trnL-trnF and trnH-psbA were analyzed. A phylogeny was reconstructed using neighbor-joining, maximum parsimony in PAUP*, and likelihood criteria in RAxML, and Bayesian inference in MrBayes. The phylogeny with Agave missionum and Agave attenuata as outgroup taxa indicates that Pleomele is mixed with Dracaena. This study provides the first phylogenetic reconstruction with taxonomic sampling of the Dracaena and Pleomele to resolve their questionable placement. The relationships of the climate change adaptation, biogeography, and conservation with the two plant genera will be further discussed in this study. Some suggestions for the benefits of the biodiversity and natural resource conservation in Himalaya regions will be addressed. One significant contribution of this research will be in promoting molecular taxonomy to solve problems in systematics especially in cases when the classification is in debate. Key-words: Phylogeny; chloroplast DNA; Asparagaceae; Dracaena; Pleomele. DOI: 10.3126/botor.v7i0.4385 Botanica Orientalis – Journal of Plant Science (2010) 7: 64-72